Clinical Characteristics, Mortality, Cardiac Hospitalization, and Ventricular Arrhythmias in Patients Undergoing CRT‐D Implantation: Results of the ACTION‐HF Study. (6th November 2012) - BOTTO, GIOVANNI LUCA; DICANDIA, COSIMO DAMIANO; MANTICA, MASSIMO; ROSA, CONCETTO LA; D'ONOFRIO, ANTONIO; BONGIORNI, MARIA GRAZIA; MOLON, GIULIO; VERLATO, ROBERTO; VILLANI, GIOVANNI QUINTO; SCACCIA, ALBERTO; RACITI, GIOVANNI; OCCHETTA, ERALDO
<x xml:space="preserve">Abstract</x> CRT Patient Characteristics and Outcomes. Introduction: The characteristics and outcomes of patients who undergo cardiac resynchronization therapy (CRT) device implantation in current clinical practice may differ from those of reference trial populations. Study objectives were to assess 2‐year outcomes in a population implanted with a CRT plus defibrillator device in accordance with the standard of care and to evaluate any independent association between clinical variables and outcome. Methods and Results: A total of 406 patients enrolled at 35 centers in Italy were followed up prospectively for 2 years. All patient management decisions were left to the treating physician's discretion, in accordance with clinical practice. ACTION‐HF patients had a better baseline clinical status than patients enrolled in the COMPANION study: shorter HF history (1 vs 3.5 years, P < 0.01), less advanced NYHA functional class (III–IV: 73% vs 100%, P < 0.01), higher LVEF (26% vs 21%, P < 0.01), higher SBP (122 vs 112 mmHg, P < 0.01), and less diabetes (27% vs 41%, P < 0.01). This status was reflected in lower mortality (11.5% vs 26%) and a lower incidence of appropriate ICD shocks (12.1% vs 19.3%). AF history was an independent predictor of the combination of all‐cause mortality and cardiac‐cause hospitalization (HR: 3.31; P < 0.001). Recurrent or new atrial arrhythmias were independently associated with the development of ventricular arrhythmias (HR: 3.4; P < 0.001). Conclusions : This population appears clinically less compromised and had a lower incidence of adverse clinical outcomes than those of reference trials. However, we recorded a substantial burden of atrial arrhythmias, which was independently associated with a higher incidence of ventricular arrhythmias. (J Cardiovasc Electrophysiol, Vol. 24, pp. 173‐181, February 2013)